Toward a Hybrid Behavioristic–Humanistic Framework for Islamic EFL Pedagogy: A Conceptual Literature Review - Nora, Wiwit Engrina; Aprison, Wedra (Ahlussunnah: Journal of Islamic Education, 2025)
English as a Foreign Language (EFL) pedagogy continues to evolve amid rapid digital transformation and shifting educational priorities. Classic learning theories such as behaviorism and humanism remain influential, yet they have traditionally been treated as competing paradigms rather than complementary foundations for instructional design. This conceptual literature review explores the theoretical duality between behavioristic and humanistic approaches in EFL learning and examines their intersection with Islamic educational philosophy. A systematic content analysis of recent scholarly publications (2019–2024) was conducted using thematic coding procedures to identify convergence, divergence, and emerging hybrid models. The findings reveal that behaviorism contributes significantly to linguistic accuracy, controlled practice, and measurable performance, whereas humanism supports intrinsic motivation, communicative confidence, and socio-emotional well-being. Increasingly, modern EFL classrooms, particularly digital and AI-assisted environments implicitly combine structured reinforcement with learner-centered engagement. Islamic pedagogy, through concepts such as ta’dib, tarbiyah, tikrar, and tadabbur, historically balances discipline and holistic growth, demonstrating strong alignment with an integrated theoretical stance. The study proposes a Hybrid Behavioristic–Humanistic EFL Pedagogical Framework emphasizing balanced development of accuracy and fluency grounded in ethical and cultural values. This framework advances theoretical discourse, offers practical guidance for EFL practitioners, and highlights implications for Islamic education settings. Future empirical studies are encouraged to validate and operationalize the model in real classroom contexts.